Sosialisasi Dan Penerapan Sistem Informasi Berbasis Web Pada Musholla Nurul Huda - Nur Rahman, Muhammad; Budiman, Arianda; Taufiqurrohman, Rifqi; Anas, Abdilah; Riandro Raul, Ignasius; Firmansyah, Iqbal; Aji Prihantoro, Bastian; Halawa, Firima; Rosandi, Andri; Prasetyo, Bayu (LOGIC : Jurnal Ilmu Komputer dan Pendidikan, 2023)
In the modern era like today, technological advances are very fast. Especially in the delivery of information quickly, actual and without physical contact (especially during a pandemic like now). information to inside and outside parties quickly In this PKM Activity this time, we want to implement a Web-based Information System Application at the Nurul Huda Mosque which aims to adjust to this Digital era and present, deliver data quickly via the Internet. An application / web system was created to make it easier for the whole community to access information about the Nurul Huda prayer room through each user's gadget by utilizing the currently available internet, so that all local people get the latest information about the Nurul Huda prayer room. Hopefully it can continue to grow and always provide useful information for all the surrounding community and even those who are far away. We have made an application / web system to make it easier for all people to access information about the Nurul Huda prayer room through each user's gadget by utilizing the internet that is currently available. this, so that all local people get the latest information about the Nurul Huda prayer room. Hopefully it can continue to grow and always provide useful information for all the surrounding community and even those who are far away.